Amyloid‐related imaging abnormalities (ARIA): diagnosis, management, and care in the setting of amyloid‐modifying therapy - Rade B. Vukmir (Annals of Clinical and Translational Neurology, 2024)
Abstract Amyloid‐related imaging abnormalities, were originally described by dementia care experts. The wider use of aducanumab and now lecanemab warrant broader understanding by the health care provider continuum. The optimal care approach for patients with Alzheimer's dementia, treated with amyloid‐targeted therapy, includes proper clinical diagnosis, complication surveillance, specific imaging protocols, expert specialty consultation, integrated treatment strategies, and proper facility system planning. Improved awareness and understanding of amyloid‐modifying therapy, both benefits and potential complications, among the health care provider continuum is paramount to the success of complex care programs. Specifically, recognition of treatment high risk, high benefit groups, and the interface of concurrent antiplatelet and anticoagulation. This integrated acute, specialty, and primary care approach should improve patient care quality and outcome.